Controversial issues of application of the presumption of rightness of the audited entity (taxpayer) - Pilipenka, Aleksandr A. (Journal of the Belarusian State University. Law, 2025)
The article analyses theoretical and applied aspects of application of the presumption of the rightness of the audited entity (taxpayer), which provides for the adoption of a decision in the event of ambiguity or vagueness of the provisions of legislative acts in its favour. A conclusion about the primacy of application of the presumption in question compared to taxpayers’ requests for clarification of tax legislation is made. Changes in legislation aimed at optimising the legal regulation of the presumption of the rightness of the audited entity (taxpayer) are proposed.
Keywords: taxpayer; presumption; presumption of the rightness of the taxpayer; written explanations; control measures